(3TQM GdQVi Ydi GdcGajIs - (3GdESJQGHGPj GdSefGFj GdfLaj GdQVj, GdQVj, fLe GdOjf, eMeO Hf GdMSf, J (B686 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3GdcdeI daX hVY deYfi eaQO GYde Cf GdcdeI eaQO Gdcde eKd JeQ hJeQI hdjS GdeLQO ef GdJGA ef gPG GdfhY LeYG dPj GdJGA ceG jLjA JMbjbg aj HGH GdLeY Hd gh LfS Mbg Cf jbY (B...s
(3BNQgG (B:s
... (3Ef cGf GdBNQ SGcfG UMjMG JfhjfG cGf Gh ZjQg hfMh gPG (B.. (3aEPG CQOJ Sja ef Ufag cjJ hcjJ hjbhd aj bO aYd (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\86s
(3cTa GdXfhf (B2\1370s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs